Prace Komisji Prawa Międzynarodowego ONZ nad klauzulą największego uprzywilejowania (knu) - próba krytycznej oceny: [Works of the UN Committee of International Law on the most-favoured-nation clause] (Studia Prawnicze / The Legal Studies, 1983)
Numerous problems connected with the most-favoured-nation clause, widely discussed in the world literature, have been enriched by a new aspect, namely the results of works of the International Law Commission on the most-favoured-nation clause carried out in the years 1961-1978. The present article deals with these problems. First, it explains why the Commission became interested in the clause and presents remarks on the structure of the draft.The Commission adopted a draft convention on the most-favoured-nation clause which includes many controversial solutions. The article points especially to those solutions of the Commission which may influence the evaluation of the convention by particular states. They are: definitions of basic notions, unconditional character of the most-favoured-nation clause, application of the most-favoured-nation clause in relations with developing countries, the problem of exception of customs unions. In particular, the scope of exception from the most-favoured-nation clause, which the Commission included into the draft, may rise various doubts, especially in the light of the GATT provisions as it may result in conflicting economic interests of the states.The author also discusses the relation of the function of codification and function of progressive development of international law in relation to the most-favoured-nation clause.The attitudes of particular states towards the results of works. of the Committee have also been mentioned, which will influence their adoption of the convention of the most-favoured-nation clause.